Knowledge, Attitude and Practices of Diabetes Mellitus among Patients Visiting Out-Patient Department at A Rural Health Centre of Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2021)
Background : Diabetes Mellitus (DM) is a disorder in which the body does not produce enough or respond normally to inculin causing blood sugar levels to be abnormally high. To assess the knowledge, attitude and practices regarding diabetes mellitus and their associated factors among diabetic patients visiting outpatient department of a primary care setting at a rural health center. Materials and methods: A questionnaire based crosssectional survey was carried out in the Outpatient Department of a primary level hospital in a poor resource country from February to November 2021. A total of 384 patients aged ³30 years of either gender with known diabetes mellitus type 2 were included in the study using systematic random sampling technique and interviewed using a pretested structuredquestionnaire. Data were analyzed on Statistical Package for Social Sciences (SPSS) version 21 and inferential analysis was performed using chi-square test. The study duration spanned over 9 months.Results: The study results showed that 257 (66.9%) of the participants had adequate knowledge, 165 (43.0%) had adequate attitude while only 105 (27.3%) had adequate practices related to diabetes mellitus. Moreover, adequateness of attitude was statistically significantly associated with age (p=0.001) and education (p=0.016) while that of practices was also statistically significantly associated with age (p=0.001) and education (p